Enhanced Immunogenicity of Foot-and-Mouth Disease Virus-like Particles Using a Water-in-Oil-in-Water Adjuvant - Yujie Zhou; Wenzhu Yin; Zhidong Teng; Yanyan Zhao; Yu Lu; Yingjuan Qian; Bihua Deng (Vaccines)
Background: Foot-and-mouth disease (FMD) causes significant economic losses, prompting vaccination as a primary control strategy. Virus-like particles (VLPs) have emerged as promising candidates for FMD vaccines but require adjuvants to enhance their immunogenicity. In this study, we evaluated the immunogenicity of a VLP-based vaccine with a water-in-oil-in-water (W/O/W) emulsion adjuvant, named WT. Methods: The WT adjuvant was mixed with FMD VLPs to form the VLPs+WT vaccine. The size and stability of the vaccine were analyzed. BALB/c mice were immunized with the VLPs+WT vaccine, and immunological responses were assessed through antibody measurements, cytokine profiling, and gene expression analysis. In addition, splenic lymphocyte proliferation and signaling pathways were examined. Results: The VLPs+WT vaccine exhibited a homogeneous size of 324.60 ± 2.30 nm and a viscosity of 8.76 mPa·s, indicating good stability. Immunized mice showed steady weight gain and no organ abnormalities. Compared to the VLPs group, the VLPs+WT group induced significantly higher levels of specific antibodies that persisted for 12 weeks, similar to the commercial VLPs+ISA201 vaccine. The VLPs+WT vaccine also enhanced the secretion of Th1-related (IgG2a, IFN-γ) and Th2-related (IgG1, IL-4) molecules. WT stimulated splenic lymphocyte proliferation and differentiation, primarily activating B-cell receptor signaling and phagosome pathways. It also upregulated genes associated with MHC and interferon stimulation while promoting the expression of MyD88, PI3K, AKT, p65, and p-p65 proteins. Conclusions: These findings suggest that WT is an effective adjuvant for FMD VLP-based vaccines, with potential for improving vaccine efficacy.